The Role of Aisyiyah in Fostering Family Maturity in Magelang Regency - Yusron Masduki; Yusutria; Ru’iya; Abdul Hopid (At Turots: Jurnal Pendidikan Islam, 2023)
This research is intended to describe Aisyiyah's role in instilling family maturity in Magelang Regency. The subjects of this study included 7 Aisyiyah administrators in Magelang district, using interview, in-depth, observation and documentation methods. Data analysis uses descriptive analysis in fostering family maturity. In fostering family maturity by providing training, counseling and coaching and conducting workshops. The innovation of fostering family maturity is based on the road map of the work program of the Regional Leadership of Aisyiyah, Magelang Regency. This family maturity development innovation is a combination of the top-bottom model and the bottom-up model. The results of the study show that the combination of the top-up model and the bootom-up model is more effective, because it can combine what is needed by the community and Aisyiyah administrators in maturing the family.